Trust-based clustering for multicast key distribution scheme in ad hoc network (TBCMKDS). (1st January 2011) - Palanisamy, V.; Annadurai, P.
In wireless and distributed nature of ad hoc networks, security has become a more sophisticated problem than security in other networks, due to the open nature and the lack of infrastructure of such networks. TBCMKDS discussed in this paper addresses the key management issues encountered in ad hoc networks. TBCMKDS is inspired by the control, accessibility and scalability characteristic of cluster architecture in distributed systems. The system builds cluster and spans the entire network with different clusters. The nodes within the cluster select a cluster head using degree of neighbours, node identification and trust, mimicking the human neighbour enquiry model. After a detailed analysis on various existing key management schemes, the proposed scheme freezes with the modified version of web of trust approach. elliptic curve cryptography (ECC) is used for key pair and certificate generation, since ECC provides higher security with lesser key size.